The complementary effect of market orientation and resource orientation on new product success: an empirical study of Malaysian manufacturing firms - Siti Norhasmaedayu, Mohd Zamani (2016)
The importance of developing new product in Malaysia has started to gain the academician and practitioner’s attention when the country moved its economic dependency from agriculture to manufacturing. However, empirical studies on the success of new products are limited and still in infancy stage in the Malaysian context. Researchers and manufacturers agreed that market orientation and resource orientation are among the crucial factors for new product success. Compared to individual orientation, researchers agreed that the combined effect of both orientations will lead to better new product success. However, the studies on the combined effect of market orientation and resource orientation on new product success in different environmental settings are very scarce. Thus, the relationship between the complementary effect of both orientations and new product success are not clearly defined. This study examines the effect of market orientation and resource orientation; assessing by single (or individual) and combined approach, on the success of new products of Malaysian manufacturers which mediated by product quality and innovation speed and moderated by market turbulence and technological uncertainties. This study applied mix-methods approach for quantitative as primary method and qualitative as secondary method. The results indicate that market orientation and resource orientation affect new product success directly or indirectly through product quality and innovation speed while the relationship between the complementary-effect of high market orientation-high resource orientation on the success of new product is vary across environmental uncertainties. The results reveal the importance of selecting appropriate strategy to be implemented by the firms, especially in different level of environmental uncertainties. Future research should focus on the multiple dimensions on the success of new products, and additional strategic orientation and environmental uncertainties as part of the research framework.